Evaluation of fracture resistance of maxillary premolars with class II mod cavities restored with fiber-reinforced composite and Cention N — An in vitro study - Leela Naga T. Pavani; Krishnaveni M Marella; Srividya Putta; M K Ramya (Journal of Dr. NTR University of Health Sciences, 2022)
Aim: The purpose of this in vitro study is to assess the influence of fiber-reinforced composite (FRC) and Cention N on the fracture resistance of maxillary premolars with class II mesio-occluso-distal (MOD) cavities. Materials and Methods: Forty-five freshly extracted human maxillary premolar teeth were collected and embedded in an acrylic cylinder up to 2.0 mm below the cementoenamel junction (CEJ) using self-cure acrylic resin. MOD cavities were prepared with continuous water cooling using a high-speed handpiece and a diamond bur. Samples were then divided randomly into three experimental groups with 15 teeth each according to the respective composite: Group A: teeth were left intact; Group B: fiber-reinforced composite (FRC); and Group C: Cention N. All groups were stored in water at 37°C for 24 hours and thermocycled 500 times between 5°C and 55°C. All specimens were subjected to compressive axial loading in a universal testing machine using a steel bar which was placed centrally to the occlusal surface and applied in parallel to the long axis of the tooth until fracture occurred. Statistical Analysis: One-way analysis of variance (ANOVA) and Tukey's post hoc test were used to analyze the results. Results: In the present study, Cention N showed significantly high fracture resistance compared to fiber-reinforced composite. Conclusion: Among the test specimens, Cention N showed significantly high fracture resistance.